Interleukin 27 is a novel cytokine with anti-inflammatory effects against spondyloarthritis through the suppression of Th17 responses - Jouhault, Quentin; Cherqaoui, Bilade; Jobart-Malfait, Aude; Glatigny, Simon; Lauraine, Marc; Hulot, Audrey; Morelle, Guillaume; Hagege, Benjamin; Ermoza, Kétia; El Marjou, Ahmed; Izac, Brigitte; Saintpierre, Benjamin; et al. (Frontiers in Immunology, 2023)
Spondylarthritis (SpA) development in HLA-B27/human β2-microglobulin transgenic rat (B27-rat) is correlated with altered conventional dendritic cell (cDC) function that promotes an inflammatory pattern of CD4+T cells, including a biased expansion of pro-inflammatory Th17 population and imbalance of regulatory T cells cytokine profile. Transcriptomic analysis revealed that cDCs from B27-rats under express IL-27, an anti-inflammatory cytokine which induces the differentiation of IL-10+ regulatory T cells and inhibits Th17 cells. Here, we first investigated whether in vitro addition of exogenous IL-27 could reverse the inflammatory pattern observed in CD4+ T cells. Next, we performed preclinical assay using IL-27 to investigate whether in vivo treatment could prevent SpA development in B27-rats. in vitro addition of IL-27 to cocultures of cDCs and CD4+ T cell subsets from B27-rats reduced IL-17 and enhanced IL-10 production by T cells. Likewise, IL-27 inhibited the production of IL-17 by CD4+ T cells from SpA patients. Interestingly, in vivo treatment with recombinant IL-27 starting before SpA onset, inhibited SpA development in B27-rats through the suppression of IL-17/TNF producing CD4+ T cells. Overall, our results reveal a potent inhibitory effect of IL-27 and highlight this cytokine as a promising new therapeutic target in SpA, especially for SpA patients non responders to currently approved biotherapies.